2018
DOI: 10.1111/nbu.12307
|View full text |Cite
|
Sign up to set email alerts
|

The portion size effect and overconsumption – towards downsizing solutions for children and adolescents

Abstract: Portion sizes of foods offered to consumers have increased at the same time as overweight and obesity levels have risen. It has been suggested that large portions of high energy density (HED) foods increase total energy intake and that this is not compensated for in the short-to medium-term, potentially promoting weight gain. In the laboratory setting, offering large portions of HED foods increases overall energy intake in both children and adults. This phenomenon is known as the portion size effect (PSE), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
3
36
0
1
Order By: Relevance
“…) and higher parent‐reported food responsivity (Kling et al . 2016a) have also been associated with a stronger PSE, suggesting that individual differences related to food approach behaviours are likely to underpin a child's sensitivity to larger portion sizes (Hetherington & Blundell‐Birtill ).…”
Section: What Is the Evidence For Good Self‐regulation Of Eating Behamentioning
confidence: 99%
“…) and higher parent‐reported food responsivity (Kling et al . 2016a) have also been associated with a stronger PSE, suggesting that individual differences related to food approach behaviours are likely to underpin a child's sensitivity to larger portion sizes (Hetherington & Blundell‐Birtill ).…”
Section: What Is the Evidence For Good Self‐regulation Of Eating Behamentioning
confidence: 99%
“…), sometimes termed the ‘portion size effect’. However, it is not clear whether reducing portion sizes leads to reduced energy consumption at that meal and, if so, whether there is any compensatory increase in intake at subsequent meals (Hetherington & Blundell‐Birtill ).…”
Section: Evidence From Experimental Studies: the Portion Size Effectmentioning
confidence: 99%
“…There is considerable evidence that offering large portion sizes of energy-dense foods can lead to increased energy intake at that eating occasion (Hollands et al 2015), sometimes termed the 'portion size effect'. However, it is not clear whether reducing portion sizes leads to reduced energy consumption at that meal and, if so, whether there is any compensatory increase in intake at subsequent meals (Hetherington & Blundell-Birtill 2018).…”
Section: Evidence From Observational Studies: Dietary Patternsmentioning
confidence: 99%
“…Numerous studies have shown that people of all ages, perhaps with the exception of very young children, eat more when portion sizes are larger (Hetherington & Blundell‐Birtill ) and it has been estimated that the effect of larger portion sizes across the diet in adults could be equivalent to a 12–16% increase in daily energy intake from food per day (Hollands et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that people of all ages, perhaps with the exception of very young children, eat more when portion sizes are larger (Hetherington & Blundell-Birtill 2018) and it has been estimated that the effect of larger portion sizes across the diet in adults could be equivalent to a 12-16% increase in daily energy intake from food per day (Hollands et al 2015). In an economic analysis of cost-effective strategies to reduce obesity, portion size reduction (by food and drink producers, in restaurants and workplace canteens) was identified as the most cost-effective of 18 categories of intervention to help reduce obesity (McKinsey 2014).…”
Section: Introductionmentioning
confidence: 99%